Legal Certainty Regarding The Validity Period of Halal Certificates In Indonesia - Kuntari Angrani; Yenny Eta Widyanti; Siti Rohmah (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Regulations regarding the validity period of halal certificates in Indonesia have undergone significant changes following the enactment of Law Number 6 of 2023 concerning Job Creation. Previously, Law Number 33 of 2014 concerning Halal Product Assurance stipulated that halal certificates are valid for four years and must be renewed periodically as a form of state supervision of the consistency of product halalness. However, after the amendment through the Job Creation Law, halal certificates are declared valid as long as there are no changes in the composition of ingredients and/or halal product processes. This study aims to analyze the shift in regulations regarding the validity period of halal certificates and assess the legal certainty of these regulations based on Gustav Radbruch's theory. The novelty of this research lies in its critical analysis of the transition from a periodic monitoring model to a perpetual halal certification model within the framework of legal certainty, justice, and utility. This research is a normative legal study using a legislative approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials collected through literature studies and analyzed descriptively and qualitatively. The results show that changes in regulations regarding the validity period of halal certificates reflect a shift in legal orientation from a periodic monitoring system to administrative simplification and economic efficiency. While these changes provide administrative and economic benefits for businesses, they also create legal challenges in the form of unclear norms, weak post-certification oversight, and the potential for reduced legal protection for Muslim consumers. According to Gustav Radbruch's theory, these regulations tend to prioritize utility over legal certainty and justice. Therefore, regulatory harmonization and strengthening of the oversight system are needed to ensure optimal legal protection for Muslim consumers in Indonesia.